Trends in demographic and employment characteristics of US emergency medical technicians and paramedics, 2011–2019 - Rebecca E. Cash; Jonathan R. Powell; Gregory A. Peters; Scott A. Goldberg; Ashish R. Panchal; Carlos A. Camargo Jr. (Journal of the American College of Emergency Physicians Open)
Abstract Background Describing the US emergency medical services workforce is important to understand gaps in recruitment and retention and inform efforts to improve diversity. Our objective was to describe the characteristics and temporal trends of emergency medical technicians (EMTs) and paramedics in the United States. Methods We performed a repeated cross‐sectional evaluation of US Census Bureau's American Community Survey 1‐year Public Use Microdata Sample data sets from 2011–2019. We included respondents working as an EMT or paramedic. Survey‐weighted descriptive statistics of demographic and employment characteristics were calculated. Trend analysis was conducted using joinpoint regression to estimate slope and annual percent change (APC). Results The total estimated number of EMTs and paramedics in the United States increased from 216,310 (95%CI 204,957–227,663) in 2011 to 289,830 (95%CI 276,918–302,743) in 2019 (APC 3.0%; 95%CI 1.4%, 4.7%). There was a slight increase in the proportion of females (2011, 31%; 2019, 35%). There was a significant decrease in proportion of non‐Hispanic whites (2011, 80%; 2019, 72%; APC −1.5%; 95%CI −2.0%, −0.9%) with concurrent increases in other racial/ethnic groups (e.g., Hispanics, 2011, 10%; 2019, 13%). About half worked >40 hours per week, with little change over time. Between 15% and 18% lived and worked in different states, and about 40% traveled ≥30 minutes to their workplace. Conclusions The number of EMTs and paramedics actively working in EMS as their primary paid occupation has increased over time. However, there have been only modest changes in their demographic diversity.